Environment sensing technology of underwater ROV based on artificial siding - Wenhui Wang; Fumeng Ye; Rufei He (PLoS ONE, 2025)
The underwater environment has the characteristics of high pressure and low temperature, which limits the performance of the sensor, and there are inaccuracies or distortions in the measurement data, resulting in errors and uncertainties in the environmental perception results. Therefore, the environment sensing technology of underwater ROV based on artificial side line is proposed. According to the artificial side line structure, the underwater terrain environment perception principle is constructed, and each characteristic parameter is counted. The underwater acoustic sensor network communication model was constructed, the sound field disturbance based on the artificial side line normalization was analyzed, and the impact response function and response time approximation were calculated by using the transmitting array and receiving array to obtain the fixed point of the underwater moving target and realize underwater ROV environment perception. The experimental test results show that under the artificial side line, the predicted value of ROV environment sensing technology is always floating around the true value curve, and the positioning performance is good. Under different conditions, the measurement error decreases to less than 1%. When controlling the environment perception position of underwater ROV, the obtained coordinates are basically consistent with the expected coordinates, realizing the perception of underwater terrain environment and target positioning, which has a wide application prospect for underwater exploration, Marine scientific research, diving operations and other fields. In future studies, the statistical methods of characteristic parameters will be continuously optimized to improve the accuracy and stability of statistical results. At the same time, the introduction of additional environmental parameters will also be considered to more fully reflect the changes in the underwater environment.